ANALISIS KESIAPAN PEMERINTAH DAERAH DALAM PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL (Studi pada Pemerintah Daerah Kabupaten Bondowoso) - Arif, Moh. Mashudi; Putra, Hendrawan Santosa; Kurrohman, taufik (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2013)
The purpose of this study was to describe the eventual regency government readiness in implementing SAP accrual. The indicators used to assess the readiness include commitment/ integrity, human resources, facilities, and information systems. In addition this study will also describe the conditions and obstacles that occur during the preparation period and will provide an overview of SAPs strategy of accelerating the implementation of accrual through internal and external analysis. This study used a qualitative approach with quantitative tools as a medium for describing readiness. The data used is primary data obtained from observations, interviews and questionnaires. The results of this study explains that when viewed in terms of commitment, human resources, facilities, and information systems the regency government can be categorized quite ready in the analysis in general. This indicates that most on education still has the ability and capacity to implement accrual-based SA . based on the percentage of readiness on education , 50 % on education categorized as âlessâ, while the âgoodâ only 3.8 % remaining in the category of âprettyâ by 46.2 %. The analysis of each variable is also not much different, of the four variables used commitment, human resources, and infrastructure criteria entered into the âprettyâ and only variables or indicators of system information that has the criteria of âgoodâ. The results of the road map analysis explaining that the regency government has some weaknesses and obstacles in implementing SAP accrual. The weaknesses include the lack of qualified human resources and infrastructure as well as less than the maximum support from the leadership on education. Strategies that can be used by the regency government as a form of accelerated accrual of SAP implementation, namely the aggressive strategy. Keywords: SAP Accrual, Readiness, Commitment, Human Resources, Infrastructure, Information Systems